A performance de crianças pequenas em atividades de exploração do mundo em uma instituição de educação infantil: refletindo o vínculo entre educação infantil e ensino de ciências - Alexandre Fagundes Pereira (2018)
The relationship between Education in Science and Early Childhood Education is very incipient. There are few studies that deal with this issue, always based on approaches that transpose research conceptions with older children (elementary and middle school). Acting in this interface (Early Childhood Education and Science Education) and based on the theoretical-analytical framework of the Actor-Network Theory (ANT), the present research had as its main objective to investigate the performance of young children (five years) in physical and natural world exploration activities. For this, we investigated a group of five-year-old children involved in a research project related to the theme "What's in the Sky?" at a Unidade Municipal de Educação Infantil (UMEI) in Belo Horizonte during the first half of 2015. These data were obtained through a database from a survey contemplated by a bidding document by Brazilian agencies to promote research (Capes / Fapemig). In the analysis of the data we described the meetings that were destined to the research project of the class. The results of this work enabled us to reflect on the role played by children, adults and the scientific content present and highlight the possibilities of working with the sciences, from a child perspective